2010
DOI: 10.1007/s11633-010-0522-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved exponential stability criteria for uncertain neutral system with nonlinear parameter perturbations

Abstract: This paper investigates the problem of robust exponential stability for neutral systems with time-varying delays and nonlinear perturbations. Based on a novel Lyapunov functional approach and linear matrix inequality technique, a new delay-dependent stability condition is derived. Since the model transformation and bounding techniques for cross terms are avoided, the criteria proposed in this paper are less conservative than some previous approaches by using the free-weighting matrices. One numerical example i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Remark 15. It should be also mentioned that the result obtained in Theorem 10 is delay-range-dependent and decay rate-dependent stability condition for (13), which is less conservative than the previous ones and will be verified in Section 4. Although the large number of introduced free weighting matrices may increase the complexity of computation, utilizing the technique of free weighting matrices would reduce the conservativeness.…”
Section: Remark 12mentioning
confidence: 64%
See 3 more Smart Citations
“…Remark 15. It should be also mentioned that the result obtained in Theorem 10 is delay-range-dependent and decay rate-dependent stability condition for (13), which is less conservative than the previous ones and will be verified in Section 4. Although the large number of introduced free weighting matrices may increase the complexity of computation, utilizing the technique of free weighting matrices would reduce the conservativeness.…”
Section: Remark 12mentioning
confidence: 64%
“…From Tables 5, 6, and 7, we consider = 0, = 0.5, and = 0.9 and obtain the maximum upper bound of delay 2 = 1.5167, 2 = 1.0643, and 2 = 0.7136, respectively, in this paper by setting = 0.1, while the maximum upper bound of delay 2 = 1.2999, 2 = 0.9442, and 2 = 0.5471, respectively, for [44], the maximum upper bound of delay 2 = 1.4008, 2 = 1.0120, and 2 = 0.6438, respectively, for [13]. The results are also given by setting = 0.3, = 0.5, = 0.7, and = 0.9, and it is found that the maximum upper bound of delay in this paper is larger than those in [13,44].…”
Section: Numerical Examplesmentioning
confidence: 86%
See 2 more Smart Citations
“…Recently, many researchers have studied the stability problem for neutral systems with time-varying delays and nonlinear perturbations have appeared [29,31]. Furthermore, the convergence rates are essential for the practical system; then the exponential stability analysis of time delay systems has been favorably approved in the past decades; see, for example, [3,9,10,14,[18][19][20][21][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%